2020
DOI: 10.3390/en13051171
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Gas Composition Prediction for Underground Coal Gasification Using a Thermochemical Equilibrium Modeling Approach

Abstract: Underground coal gasification (UCG) is an in situ conversion technique that enables the production of high-calorific synthesis gas from resources that are economically not minable by conventional methods. A broad range of end-use options is available for the synthesis gas, including fuels and chemical feedstock production. Furthermore, UCG also offers a high potential for integration with Carbon Capture and Storage (CCS) to mitigate greenhouse gas emissions. In the present study, a stoichiometric equilibrium m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The kinetic modeling results of Perkins and Sahajwalla showed good results (relative inaccuracy range: the main gas component was 0.00% to 19.19%; LCV was 6.52%) in comparison with the Centralia LBK-1 field test data. 35 The thermodynamic UCG model of Klebingat et al showed that the relative inaccuracy range for the main gas single compounds ranged between 4.32% and 9.95%; the relative inaccuracy for the synthesis gas LCV was found to be relatively low (6.60%) in comparison with the Hanna I field trial study. But the relative inaccuracy range for the main gas single compounds was between 5.88% and 18.6% and the relative inaccuracy for the synthesis gas LCV was 21.7% compared to the Centralia PSC field trial study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The kinetic modeling results of Perkins and Sahajwalla showed good results (relative inaccuracy range: the main gas component was 0.00% to 19.19%; LCV was 6.52%) in comparison with the Centralia LBK-1 field test data. 35 The thermodynamic UCG model of Klebingat et al showed that the relative inaccuracy range for the main gas single compounds ranged between 4.32% and 9.95%; the relative inaccuracy for the synthesis gas LCV was found to be relatively low (6.60%) in comparison with the Hanna I field trial study. But the relative inaccuracy range for the main gas single compounds was between 5.88% and 18.6% and the relative inaccuracy for the synthesis gas LCV was 21.7% compared to the Centralia PSC field trial study.…”
Section: Discussionmentioning
confidence: 92%
“…The results of the main gas components and LCVs were consistent with the measured data, and the maximum deviation was less than 10% (relative inaccuracy: the main compound was 0.2% to 9.4%; LCV was 0.4% to 2.2%). The kinetic modeling results of Perkins and Sahajwalla showed good results (relative inaccuracy range: the main gas component was 0.00% to 19.19%; LCV was 6.52%) in comparison with the Centralia LBK‐1 field test data 35 . The thermodynamic UCG model of Klebingat et al showed that the relative inaccuracy range for the main gas single compounds ranged between 4.32% and 9.95%; the relative inaccuracy for the synthesis gas LCV was found to be relatively low (6.60%) in comparison with the Hanna I field trial study.…”
Section: Discussionmentioning
confidence: 93%
“…The unique research results are invaluable for modeling various aspects of the UCG process and designing the process in real conditions. A number of examples of the application of the results of experimental research for the implementation of model works, including designing automated control systems, are described in the literature [44][45][46].…”
Section: Process Balance Datamentioning
confidence: 99%
“…The results showed the positive impact of the steam addition into the gasification agent to increase the hydrogen and carbon monoxide content in syngas and increase the calorific value. A stoichiometric equilibrium model has been used to estimate the equilibrium composition of the produced gas [6]. This model is based on the Gibbs function's minimization and was used to simulate the relevant thermochemical coal conversion processes.…”
Section: Introductionmentioning
confidence: 99%